A new systematic technique for retrofit of water network - Tan, Yin ling; Manan, Zainuddin (Inderscience Publisher, 2008)
This paper presents a new systematic technique for the retrofit of existing water network based on pinch analysis. This technique, which was applied on a paper mill, consists of three main steps: Network Diagnosis, Network Retrofit and Network Evolution. Network diagnosis step provides agood understanding of the existing water network through the use of a new tool called the Concentration Block Diagram (CBD). Next, modifications based on a set of pinch rules were performed on the existing water network to achieve the preliminary retrofit design. Finally, the preliminary retrofit design will go through an evolution to generate the final retrofit scheme. A paper making process case study was utilised to demonstrate the applicability of this new methodology. The results show that 55.5% of fresh water consumption and 65.7% of wastewater generation have been reduced, respectively, for the paper mill case study.